The Effectiveness of Listen-Read-Discuss Method in Improving Student Learning Outcomes: A Quasi-Experimental Study at MA Tahfidz Qur’an Habibana - KHOIRUR ROHMAH; Fadliyatul Mardliyatin; Sigit Wahyu Nurcholik; Ijlal Dipta Azizi; M. Husen Al Farisy; KHOIRUR ROHMAH; Fadliyatul Mardliyatin; Sigit Wahyu Nurcholik; Ijlal Dipta Azizi; M. Husen Al Farisy (INTENS (International Journal of English Education and Linguistics), 2026)
Abstract This study examines how effectively the Listen-Read-Discuss (LRD) method improves student learning outcomes when compared with conventional teaching approaches. We conducted a quasi-experimental study at MA Tahfidz Qur’an Habibana, involving 20 students splitted between an experimental group and a control group (n=10 each). We collected data through pre-tests, post-tests, and calculated gain scores, then analyzed these using the Mann-Whitney U test and Wilcoxon Signed Ranks Test. Our findings reveal a big difference in learning improvement between the two groups (Asymp. Sig. = 0.000 < 0.05). The experimental group achieved a Mean Rank of 15.50, three times higher than the control group's 5.50. Students taught with LRD showed significant improvement (Sig. = 0.005 < 0.05), while those receiving conventional instruction showed no meaningful gains (Sig. = 0.286 > 0.05). These results clearly demonstrate that the LRD method outperforms conventional teaching in enhancing student learning outcomes. Keywords: Listen-Read-Discuss, learning outcomes, quasi-experimental, active learning